EFEKTIVITAS PEMBELAJARAN TREFFINGER DENGAN STRATEGI METAKOGNITIF TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA SMK - Ahmad Sayfudin; Heny Sulistyaningrum; Puji Rahayu (FKIP Unirow Tuban, 2016)
This research is motivated by the lack of ability to think creatively mathematics vocational students. As an alternative solution are teaching students with learning Treffinger with metacognitive strategies. This study aimed to test: 1) whether there is a significant difference in average ability to think creatively math class X SMK PGRI 2 Tuban in the academic year 2015/2016 the students that learned by learning Treffinger with metacognitive strategies with students that learned with conventional study; 2) learning is more effective to improve the ability to think creatively math class X SMK PGRI 2 Tuban 2015/2016 academic year among the students that learned by learning Treffinger with metacognitive strategies with students that learned with conventional learning? This type of research is an experimental research with a quantitative approach. The subjects of this study are students of class X SMK PGRI 2 Tuban in the academic year 2015/2016. The instrument used was a test of creative thinking ability in mathematics. To analyze the data in this study used the t test. The results of the study concluded that there was a statistically significant difference in average ability to think creatively math class X SMK PGRI 2 Tuban in the academic year 2015/2016 the students that learned by learning Treffinger with metacognitive strategies with students that learned with conventional learning.